Confined childhoods: Where does the body go in school? - Karla de Oliveira Santos (Universidade Estadual de Alagoas, 2021)
The body has been configured as an object of control by the State and its institutions, like the school, which tries to enclose childhoods, with the intent of forming docile and disciplined bodies, to become productive force and consumers, which serve the interests of capital. . From a theoretical reflection based on Foucauldian studies, the objective of this work is to problematize how the school, together with its apparatus, such as: pedagogical work and the curriculum, try to confine childhoods, for the formation of docile and disciplined subjects,from the control of the body and its implications on the subjectivity of the subjects. Therefore, it is important to highlight that the educational public policies of the last three years, have presented setbacks with conservative models of thinking about childhoods and, consequently, children's bodies, reinforcing mechanical and instrumentalizing practices in attendance to a homogeneous curriculum and to large-scale evaluations. , the school being responsible for the formation of docile, useful, participatory, responsible bodies, producing specific subjectivities, that is; the creation of the modern subject.